Kajian Biaya Penerapan Sistem Manajemen Keselamatan Konstruksi Pada Proyek Villa Banana di Kabupaten Badung - Yuliana, Ni Putu Indah; Suartika Putra, I Gusti Putu Adi; Yuni, Ni Kadek Sri Ebtha; Sudiarta, I Komang (Jurnal Talenta Sipil, 2024)
The implementation of the Construction Safety Management System (SMKK) is part of the management system for the implementation of Construction Work to ensure the realization of Construction Safety. The implementation of a Construction Safety Management System need a number of costs that will be part of the contract value. The purpose of the study was to determine the components of implementing SMKK, the amount of costs required for the implementation of SMKK and the percentage compared to the contract value. The study used quantitative descriptive methods and data collection in the form of surveys and interviews. The results showed that the required SMKK cost components are RKK preparation, socialization, promotion and training, work protective equipment, personal protective equipment, insurance, construction safety personnel, facilities, infrastructure, and medical devices, traffic equipment as well as activities and equipment related to construction safety risk control. Total cost for the implementation of SMKK in the Villa Banana Project is Rp. 86,520,255.50 with a consumable cost of Rp. 31,439,079.78 and a non-consumable cost of Rp. 55,081,175.72. The percentage of SMKK implementation costs on the contract value is 3.696% of the total project contract value which is Rp. 2,341,117,572.00.